Evaluasi Penularan Filariasis Limfatik di Provinsi Riau dan Bangka Belitung: Parasit pada Manusia dan Reservoir - Santoso Santoso; Yahya Yahya; Lasbudi Pertama Ambarita; Anif Budiyanto; Nungki Hapsari Suryaningtyas; I Gede Wempi DSP; Yanelza Supranelfy; Tanwirotun Ni'mah; Anorital Anorital; Rita Marleta Dewi (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Mass treatment and evaluation surveys of filariasis transmission were strategies in the control of lymphatic filariasis. Mass Drug Administration (MDA) stop period surveillance is required for five years before obtaining a lymphatic filariasis elimination certificate. The aim of conducting the study was to evaluate the activities of lymphatic filariasis elimination in areas that have been doing MDA for five years. During July-November 2017, fingertip blood samples of people aged five years and examination of reservoir animals was done in Riau and Bangka Belitung Province. The results of the study found that in Kuatan Singingi and Pelalawan district Mf rate was <1%, in West Bangka and Belitung districts Mf rate> 1% with all specied identified as Brugia malayi. Survey of animal reservoir obtained positive of B. malayi on two cats (Felis attus), one dog (Canis familiaris), and one monkey (Macaca fascicularis). Riau Province was not a filariasis endemic area (Mf rate <1%), while Bangka Belitung Province Mf rate was still >1%. The risk of transmission in Kuantan Singingi District was already low, while in Pelalawan regency, West Bangka and Belitung were still high.